Cryo-attenuated properties of Tilia miqueliana pericarps and seeds - Wu, Yu; Sun, Xiao Rui; Peng, Chen Yin; Shen, Yong Bao; Visscher, Anne M.; Pritchard, Hugh W.; Wang, Ming Zhu; Deng, Zhi Yun (Frontiers in Plant Science, 2023)
The interactive review of your manuscript "Cryo-attenuated properties of Tilia miqueliana pericarps and seeds" submitted to Frontiers in Plant Science, section Plant Breeding has now been activated.Reply: Thank you for your timely notification. We carefully responded to every comment and resubmit the revised manuscript on time.The reviewers recommended that you make minor amendments to your manuscript. Please respond within the next 7 days to all comments raised by the reviewers and editor in the online review forum.We are excited to receive the reviewers recommend to make minor amendments to the manuscript. Our team has been engaged in research on the dormancy breaking and seedling production of hard-shell forest seeds for nearly 20 years. We carefully responded to all comments raised by the reviewers and editor one by one.on the Reviewer tab is closed, you should submit a reply to pending comments in a new thread in the Editor tab. If necessary, you can also submit a revised version of your manuscript at that time. We encourage you to submit your documents with tracked changes to highlight the revisions.There can be more than one iteration between authors and reviewers, but only when all comments by each reviewer have been addressed successfully can the review be finalized.